Globular clusters in the Fornax cluster: A report from the FDS survey. Issue Volume 14:Issue S351(2019) (May 2019) - Cantiello, Michele; Venhola, A.; Paolillo, M.; D'Abrusco, R.; Grado, A.; Iodice, E.; Peletier, R.; Capaccioli, M.; Hilker, M.; Mieske, S.; Napolitano, N.; Riccio, G.; et al.
Abstract: The Fornax Deep Survey (FDS) is a multi-band imaging survey of the Fornax cluster of galaxies, executed with the ESO VLT Survey Telescope (VST). The survey is designed to reach unprecedented surface brightness and point-source magnitude depth over one virial radius of the cluster. The scientific objectives of the survey are numerous: the study of the galaxy luminosity function, derivation of galaxy scaling relations, determination of the properties of compact stellar systems, an accurate determination of distances and 3-D geometry of the Fornax cluster, analysis of diffuse stellar light and galaxy interactions, etc. In this contribute we give an overview on the interest of the survey on globular clusters (GC) populations, and present a report the status of the study of GCs also providing some preliminary results of our analysis, with particular regard to the two-dimensional distribution of GC candidates over ∼20 sq. degree area of Fornax centered on NGC 1399.